Atypical Femoral Shaft Fractures in Female Bisphosphonate Users Were Associated with an Increased Anterolateral Femoral Bow and a Thicker Lateral Cortex: A Case-Control Study. (28th March 2017) - Jang, Seung Pil; Yeo, Ingwon; So, Sang-Yeon; Kim, Keunbyuel; Moon, Young-Wan; Park, Youn-Soo; Lim, Seung-Jae
Abstract : The purpose of our study was to investigate the radiographic characteristics of atypical femoral shaft fractures (AFSFs) in females with a particular focus on femoral bow and cortical thickness. We performed a fracture location-, age-, gender-, and ethnicity-matched case-control study. Forty-two AFSFs in 29 patients and 22 typical osteoporotic femoral shaft fractures in 22 patients were enrolled in AFSF group and control group, respectively. With comparing demographics between two groups, radiographically measured femoral bow and cortical thicknesses of AFSF group were compared with control group. All AFSF patients were females with a mean age of 74.4 years (range, 58–85 years). All had a history of bisphosphonate (BP) use with a mean duration of 7.3 years (range 1–17 years). Femoral bow of AFSF group was significantly higher than control group on both anteroposterior (AP) and lateral radiographs after age correction. Mean femoral bow on an AP radiograph was 12.39 ° ± 5.38 ° in AFSF group and 3.97 ± 3.62 ° in control group (P < 0.0001 ). Mean femoral bow on the lateral radiograph was 15.71 ° ± 5.62 ° in AFSF group and 10.72 ° ± 4.61 ° in control group (after age correction P = 0.003 ). And cortical thicknesses of AFSF group demonstrated marked disparity between tensile and compressive side of bowed femurs in this study. An adjusted lateral cortical thickness was 10.5 ± 1.4 mm in AFSF group and 8.1 ± 1.3 mm in control group (after age correction P < 0.0001 ) while medial cortical thickness of AFSF group was not statistically different from control group. Correlation analysis showed that the lateral femoral bow on the AP radiograph was solely related to lateral CTI (R = 0.378, P = 0.002 ). AFSFs in female BP users were associated with an increased anterolateral femoral bow and a thicker lateral cortex of femurs.